1999
DOI: 10.1074/jbc.274.39.27426
|View full text |Cite
|
Sign up to set email alerts
|

Relative Hypoglycemia and Hyperinsulinemia in Mice with Heterozygous Lipoprotein Lipase (LPL) Deficiency

Abstract: Lipoprotein lipase (LPL) provides tissues with fatty acids, which have complex effects on glucose utilization and insulin secretion. To determine if LPL has direct effects on glucose metabolism, we studied mice with heterozygous LPL deficiency (LPL؉/؊). LPL؉/؊ mice had mean fasting glucose values that were up to 39 mg/dl lower than LPL؉/؉ littermates. Despite having lower glucose levels, LPL؉/؊ mice had fasting insulin levels that were twice those of ؉/؉ mice. Hyperinsulinemic clamp experiments showed no effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 58 publications
2
49
0
1
Order By: Relevance
“…Most studies in ZDF animals have used crude cellular extracts and found intracellular levels of TAG to increase from <50 ng/islet in control rats to up to 1,000 ng/islet in 12-week-old ZDF animals (6,(15)(16)(17)(18)(19). Two studies using normal islets in culture have extracted the lipids before the GPO Trinder assay (34,35) are quantitatively similar to those of Zhou et al (34) and uniquely demonstrate that the presence of glucose is necessary for TAG content to increase significantly upon prolonged exposure to exogenous palmitate.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies in ZDF animals have used crude cellular extracts and found intracellular levels of TAG to increase from <50 ng/islet in control rats to up to 1,000 ng/islet in 12-week-old ZDF animals (6,(15)(16)(17)(18)(19). Two studies using normal islets in culture have extracted the lipids before the GPO Trinder assay (34,35) are quantitatively similar to those of Zhou et al (34) and uniquely demonstrate that the presence of glucose is necessary for TAG content to increase significantly upon prolonged exposure to exogenous palmitate.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were extracted as above and the organic residue was resuspended in chloroform-methanol (1:1). Quantitation of TAG was performed as described (53), using Infinity Triglyceride Reagent (ThermoScientific) in an assay based on enzymatic triglyceride hydrolysis and colorimetric measurement of liberated glycerol by coupled enzymatic reactions (25,55).…”
Section: Methodsmentioning
confidence: 99%
“…Clamp experiments were performed exactly as described previously (29). After placement of a double-lumen catheter, 3-[ 3 H]glucose was administered as a priming dose followed by an infusion of 0.04 µCi/minute for a 1-hour control period.…”
Section: Methodsmentioning
confidence: 99%